2022
DOI: 10.1590/1413-82712022270207
|View full text |Cite
|
Sign up to set email alerts
|

Escala de Identidade Acadêmica e Atlética (AAIS-Br): Adaptação e Evidências de Validade

Abstract: Resumo Este estudo objetivou adaptar e apresentar evidências de validade de construto, convergente e discriminante da Academic and Athletic Identity Scale para o contexto brasileiro. Participaram da pesquisa 303 estudantes universitários brasileiros (M =23,33 anos, DP = 4,605). A amostra respondeu a um questionário sociodemográfico, Escala de Identidade Acadêmica e Atlética, Escala de Identidade Profissional e Escala Flourishing. A análise fatorial confirmatória evidenciou que a versão brasileira da AAIS repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…Indeed, it is possible that the response to item ATI5 is perceived as being closely dependent on the response to item ATI6. It should be noted that the same pattern was observed in the Brazilian version of the AAIS [ 21 ]. Further studies are also needed to determine whether this is a culture-specific finding and whether these items need to be modified in the future.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Indeed, it is possible that the response to item ATI5 is perceived as being closely dependent on the response to item ATI6. It should be noted that the same pattern was observed in the Brazilian version of the AAIS [ 21 ]. Further studies are also needed to determine whether this is a culture-specific finding and whether these items need to be modified in the future.…”
Section: Discussionsupporting
confidence: 70%
“…Having reliable and valid instruments to assess the academic and athletic identities of SAs is therefore crucial. Based on its promising psychometric properties, as demonstrated in several international studies [ 5 , 18 , 19 , 21 ], the AAIS [ 6 ] is the only instrument recommended in a recent literature review as having the potential to become a gold standard for dual career research [ 7 ]. In addition, it is important to validate the scale with SAs from different cultures and countries in order to examine the antecedents and consequences of dual identity in different SAs support structures [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand identities interplay in the dual career context, researchers were interested in the relationship between academic (i.e., the self-definition and meaning from one's role as student and has been asserted to be central to the self-concept of students; Ewing & Allen, 2017) and athletic identity (i.e., the selfdefinition and meaning from one's role as athlete and has been asserted to be central to the self-concept of athletes; Brewer et al, 1993). Except one study conducted in Australia ( i.e., r = -.03, van Rens et al, 2019), studies examining simultaneously these two identities found a positive and significant correlation between them, ranging from .21 to .62 (Fiochi-Marques et al, 2022;Hagiwara et al, 2020;Hagiwaraa et al, 2022;Martin et al, 2021;Yukhymenko-Lescroart, 2014, 2018, 2021, 2022.…”
Section: Student-athletes Identitymentioning
confidence: 89%
“…This is the case of Yukhymenko-Lescroart (2014), who developed and validated the Athletic and Academic Identity Scale (AAIS). If some studies have proposed a validation of this scale in other languages such as Japanese (Hagiwara et al, 2020) or Brazilian (Fiochi-Marques et al, 2022), this measure is not available in French, which limits the possibility of using it with French-speaking student-athletes. The purpose of the present study was to translate the AAIS into French and examine its construct and concurrent validity with a French student-athlete sample.…”
Section: Introductionmentioning
confidence: 99%